2022
DOI: 10.3389/fpsyt.2021.713141
|View full text |Cite
|
Sign up to set email alerts
|

Brain SPECT as an Imaging Biomarker for Evaluating Effects of Novel Treatments in Psychiatry–A Case Series

Abstract: The difficulties of evaluating patients with complex neuropsychiatric conditions and prescribing appropriate treatments are well known. Imaging complements clinical assessments and allows a clinician to narrow the differential diagnosis by facilitating accurate and efficient evaluation. This is particularly relevant to neuropsychiatric conditions that are often diagnosed using a trial-and error process of exclusion. Single Photon Emission Computed Tomography (SPECT) is a functional brain imaging procedure that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
5
0
2
Order By: Relevance
“…we can see perfusion SPECT neuroimaging can serve as an objective biomarker of response to treatment ( 144 , 145 ), comorbidity ( 30 , 33 , 82 , 84 , 133 ), inherently difficult symptoms to objectify, such as pain ( 147 ), and of diagnostic masqueraders as described herein and elsewhere ( 30 , 33 , 84 , 133 , 148 ).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…we can see perfusion SPECT neuroimaging can serve as an objective biomarker of response to treatment ( 144 , 145 ), comorbidity ( 30 , 33 , 82 , 84 , 133 ), inherently difficult symptoms to objectify, such as pain ( 147 ), and of diagnostic masqueraders as described herein and elsewhere ( 30 , 33 , 84 , 133 , 148 ).…”
Section: Discussionmentioning
confidence: 68%
“…b. Recognize the value of SPECT in the monitoring or tracking of changes in brain function as a consequence of treatment (e.g., a biomarker) ( 130 , 144 , 145 ).…”
Section: Discussion and Actionable Recommendationsmentioning
confidence: 99%
“…SPECT also demonstrated specific findings in PTSD distinct from a trauma-exposed cohort (12). Perfusion SPECT has also been shown to provide objective evidence of neurophysiological changes in response to specific treatments, such as multi-watt infrared laser therapy for TBI (13), stem cell therapy for Lyme disease (14), and combined ketamine-transcranial magnetic stimulation (15). Studies have suggested SPECT scan data may improve clinical outcome by guiding treatment choices more quickly to successful strategies (4,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 95%
“…1 Physikalische Eigenschaften von häufig verwendeten Radionukliden für die Einzelphotonen-Emissions-Computertomografie (SPECT) und die Positronen-Emissions-Tomografie (PET). 111 In SPECT 13 N 1 0 m β + (100) 16 O(p,α) 13 N P E T 99 m Tc-Kern enthalten, in dem das koordinativ gesättigte 99 m Technetium(VII) in 99 m TcO -4 auf einen Oxidationszustand reduziert wurde, der für die Herstellung stabiler Komplexe für die Koordinationschemie besser geeignet ist. Am leichtesten zugänglich ist Technetium(V), wie die zahlreichen zugelassenen 99 m Technetium(V)-Radiotracer zeigen, darunter 99 m Tc-Sestamibi, 99 m Tc-Tetrofosmin, 99 m Tc-Teboroxim, 99 m Tc-Bicisat, 99 m Tc-Pentetat, 99 m Tc-Oxidronat (CH5O7P2Tc), bekannt unter den Handelsnamen Cardiolite, Myoview, Cardiotec, Neurolite, Technescan MAG3, Osteoscan HDP [13][14][15][16][17][18].…”
Section: Radionuklide Für Die Bildgebungunclassified
“…111 In SPECT 13 N 1 0 m β + (100) 16 O(p,α) 13 N P E T 99 m Tc-Kern enthalten, in dem das koordinativ gesättigte 99 m Technetium(VII) in 99 m TcO -4 auf einen Oxidationszustand reduziert wurde, der für die Herstellung stabiler Komplexe für die Koordinationschemie besser geeignet ist. Am leichtesten zugänglich ist Technetium(V), wie die zahlreichen zugelassenen 99 m Technetium(V)-Radiotracer zeigen, darunter 99 m Tc-Sestamibi, 99 m Tc-Tetrofosmin, 99 m Tc-Teboroxim, 99 m Tc-Bicisat, 99 m Tc-Pentetat, 99 m Tc-Oxidronat (CH5O7P2Tc), bekannt unter den Handelsnamen Cardiolite, Myoview, Cardiotec, Neurolite, Technescan MAG3, Osteoscan HDP [13][14][15][16][17][18]. Die ersten 3 Komplexe sind als Mittel zur Durchblutung des Herzmuskels zugelassen, während die anderen für die zerebrale Perfusion, die Nierenfunktion bzw.…”
Section: Radionuklide Für Die Bildgebungunclassified